FAITH-CONTENT OF THERAVADA: THE NATIONAL RELIGION OF CEYLON (SRI LANKA) - McKeon, Joseph (Journal of Dharma, 1989)
The aim of this paper is to examine the Scriptural foundations for Theravada Buddhism's - understanding of faith (saddhä). The Pali texts and early commentaries show that the Theravada community had a deep appreciation of the complex structure of the religious faith experience and its role in man's quest for knowledge. The community was well aware of the different levels at which faith operates; they knew how it was affected by different personality traits; how it varied in intensity ; how it grew, or how it was lost. They knew about its relationship to other functions of the mind. They also saw clearly its central and vital role in the Buddhist way of life.